Intra-articular Injection of a Dextran Polymer Combined with Antibiotic Medications for Bacterial Infective Arthritis in Dogs: 14 Cases - Lazarus, Matthew A.; Kim, Stanley E.; Lewis, Daniel D.; Johnson, Matthew D. (VCOT Open, 2021)
Objectives The aim of this study was to describe the use of an intra-articular delivery of a dextran polymer (IADP) for bacterial infective arthritis in dogs.Materials and Methods Cases of bacterial infective arthritis treated with IADP were reviewed. Resolution of infection was based on joint fluid cytology. Lameness scores, total nucleated cell counts, and per cent neutrophils were monitored throughout treatment.Results There were 14 dogs included in the study. The stifle was the most commonly affected joint. The median number of injections per dog was 3 with a median of 2 weeks between injections. Amikacin was combined with the dextran polymer in 13 cases and imipenem was used in 1 case. Concurrent oral antimicrobials were used in 12/14 cases, and surgery for infection was performed in 10/14 cases. Cytological evidence of infection resolved in 11/14 cases. Median lameness scores throughout treatment decreased from severe (grade ¾) at initial presentation to mild (grade ¼) at the final recheck. Median total nucleated cell counts and per cent neutrophils decreased from 40,000 white blood cell/µL and 91% to 2,200 white blood cell/µL and 4% respectively. A transient worsening of lameness was the main side effect documented in 5/14 cases.Conclusion Intra-articular dextran polymer combined with antimicrobials was generally well tolerated; however, the efficacy of IADP was unknown in this population since most dogs received concurrent oral antimicrobials and/or surgery.
Keywords: dextran polymer; antibiotics; bacterial infective arthritis; dog